The European Union and the Anti-Enlightenment Tradition - Ziegler, Tamas Dezso. author. aut Link
XIV, 253 p. 2 illus., 1 illus. in color.
Keywords: This book analyses EU and Member State decision-making through a constructivist perspective and claims that a kind of latent, intellectual “phantom war” is going on in Western societies. This war is fought through social practices, political debates, and policy choices for and against the values and ideals of the Enlightenment. The book accurately describes how the values of the Enlightenment and a contrary tradition, the anti-Enlightenment tradition, shape and reshape law and public policy choices in Europe, both at the level of the European Union, and its member states. The hidden war among historical phantoms affects European integration, the values, practices, and policies (including the legal background) of democracy, and the rule of law in our societies. These traditions also affect how we think about humanism and universalism, so they affect EU policies on refugees and other migrants, the role of rationality in public decision-making, and the weakening and defense of checks and balances, only to mention some crucial examples. Tamas Dezso Ziegler is Associate Professor in the Department of International Relations and European Studies, Faculty of Social Sciences, Eötvös Loránd University, Hungary.